Uniform multidrug therapy for leprosy patients in Brazil (U-MDT/CT-BR): Results of an open label, randomized and controlled clinical trial, among multibacillary patients. - Gerson Oliveira Penna; Samira Bührer-Sékula; Lígia Regina Sansigolo Kerr; Mariane Martins de Araújo Stefani; Laura Cunha Rodrigues; Marcelo Grossi de Araújo; Andrea Machado Coelho Ramos; Ana Regina Coelho de Andrade; Maurício Barcelos Costa; Patricia Sammarco Rosa; Heitor de Sá Gonçalves; Rossilene Cruz; et al. (Public Library of Science (PLoS), 2017)
BACKGROUND:Leprosy control is based on early diagnosis and multidrug therapy. For treatment purposes, leprosy patients can be classified as paucibacillary (PB) or multibacillary (MB), according to the number of skin lesions. Studies regarding a uniform treatment regimen (U-MDT) for all leprosy patients have been encouraged by the WHO, rendering disease classification unnecessary. METHODOLOGY AND FINDINGS:An independent, randomized, controlled clinical trial conducted from 2007 to 2015 in Brazil, compared main outcomes (frequency of reactions, bacilloscopic index trend, disability progression and relapse rates) among MB patients treated with a uniform regimen/U-MDT (dapsone+rifampicin+clofazimine for six months) versus WHO regular-MDT/R-MDT (dapsone+rifampicin+clofazimine for 12 months). A total of 613 newly diagnosed, untreated MB patients with high bacterial load were included. There was no statistically significant difference in Kaplan-Meyer survival function regarding reaction or disability progression among patients in the U-MDT and R-MDT groups, with more than 25% disability progression in both groups. The full mixed effects model adjusted for the bacilloscopic index average trend in time showed no statistically significant difference for the regression coefficient in both groups and for interaction variables that included treatment group. During active follow up, four patients in U-MDT group relapsed representing a relapse rate of 2.6 per 1000 patients per year of active follow up (95% CI [0·81, 6·2] per 1000). During passive follow up three patients relapsed in U-MDT and one in R-MTD. As this period corresponds to passive follow up, sensitivity analysis estimated the relapse rate for the entire follow up period between 2·9- and 4·5 per 1000 people per year. CONCLUSION:Our results on the first randomized and controlled study on U-MDT together with the results from three previous studies performed in China, India and Bangladesh, support the hypothesis that UMDT is an acceptable option to be adopted in endemic countries to treat leprosy patients in the field worldwide. TRIAL REGISTRATION:ClinicalTrials.gov: NCT00669643.